Ferroelectric Domain Engineered Photochemical Deposition for Area‐Selectable Broadband Enhancement of Quantum Dot Photoluminescence. Issue 10 (9th August 2013) - Lau, Kenny; Staude, Isabelle; Liu, Yun; Chen, Hua; Li, Zhenrong; Neshev, Dragomir N.
<x xml:space="preserve">Abstract</x> Spatially controllable and broadband enhancement of quantum dot (QD) photoluminescence is demonstrated via photochemical deposition of silver nanoparticles on a domain patterned ferroelectric, as a consequence of confining the excitation field near the silver nanoparticle and coupling of the multiple plasmonic modes with the QD emissions. These results are promising for application in multiplex detections. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>